The development of explosive strength of the lower extremities in volleyball players - Nejic, K.; Nejici, D.; Mitic, M.; Glisic, M. (XXI Scientific Conference "FIS COMMUNICATIONS 2018" in physical education, sport and recreation (Nis, Serbia, October 18-20, 2018), 2018)
The purpose of this paperwork was to collect studies up until now that have dealt with the development of explosive strength in volleyball players. For the collection, classification and analysis of targeted research was used descriptive method and theoretical analysis and research that have been reached are searched on Google Scholar, SCI, PubMed and Kobson. The paper presents 20 research. The results of the research have shown that plyometric training method is the most commonly used for the development of explosive force The results also show that the best effect for the development of explosive power is achieved by combining the plyometric training method and some other training.